2013
DOI: 10.1039/c3cp44500c
|View full text |Cite
|
Sign up to set email alerts
|

Doping induced structural changes in colloidal semiconductor nanowires

Abstract: Undoped and Mn(2+)-doped CdSe nanowires (NWs) grown by a solution-liquid-solid (SLS) method using Bi nanocatalysts have been studied by X-ray powder diffraction measurements. Except for heavily doped nanowires no measurable changes in nanowire lattice parameters were observed. The lattice parameter of heavily doped nanowires shrinks by about 0.5% compared with the undoped ones, which corresponds to a doping concentration of 1.6%. For the other samples no change in lattice parameter is measured referring to a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…However, if the CdSe nanocrystals contain a sufficient number of stacking faults as suggested by MAUD this is consistent with a smaller coherent diffracting domain size as suggested by the GSAS results. The interpretation of the X-ray diffraction data using either a mixture of zinc blende and wurtzite phases or using wurtzite with stacking faults agrees well with work published earlier. This result in combination with Ag preferentially located on tetrahedral interstitials in zinc blende as described below could indicate that Ag prefers sites in stacking faults.…”
Section: Resultssupporting
confidence: 88%
“…However, if the CdSe nanocrystals contain a sufficient number of stacking faults as suggested by MAUD this is consistent with a smaller coherent diffracting domain size as suggested by the GSAS results. The interpretation of the X-ray diffraction data using either a mixture of zinc blende and wurtzite phases or using wurtzite with stacking faults agrees well with work published earlier. This result in combination with Ag preferentially located on tetrahedral interstitials in zinc blende as described below could indicate that Ag prefers sites in stacking faults.…”
Section: Resultssupporting
confidence: 88%
“…Detailed XRD analyses indicated that the ZB-to-WZ ratio and the population of the stacking faults were increased, and the lattice parameters slightly decreased, with dopant concentration. 167 Single-wire EDS mapping established the homogeneous distribution of Mn, suggesting the uniform doping of CdSe nanowires by Mn 2+ (Figure 13a). The successful Mn doping into CdSe nanowire lattices was also confirmed by magnetic circular dichroism (MCD) spectroscopy (Figure 13b) as well as the appearance of low-temperature ferromagnetism (Figure 13c).…”
Section: Chemical Reviewsmentioning
confidence: 95%
“…The Mn precursor manganese stearate was injected together with Bi nanoparticles and TOPSe into the flask containing the Cd precursor, yielding Mn-doped CdSe nanowires with doping concentrations as high as 3.0%. Detailed XRD analyses indicated that the ZB-to-WZ ratio and the population of the stacking faults were increased, and the lattice parameters slightly decreased, with dopant concentration . Single-wire EDS mapping established the homogeneous distribution of Mn, suggesting the uniform doping of CdSe nanowires by Mn 2+ (Figure a).…”
Section: Sls Growth Of One-dimensional Colloidal Semiconductor Nanoro...mentioning
confidence: 97%
“…These nanowires exhibited unusual optical, 45,46 electronic, 47,48 and magnetic 40 properties with potential diverse applications. 48,49 The fast growth process resulted in crystal twinning and defects in the nanowires, 50,51 leading to a low uorescence QY (<1%) which could be improved by more than three times through coating with a wide-band-gap shell. 52 Despite monodispersity, high QY, and stability, these QDs generated in organic solvents are normally hydrophobic and have to be modied in order to be water-soluble and biocompatible for bioapplications.…”
Section: Synthesis Of Monodisperse Qds With High Qysmentioning
confidence: 99%